PENGARUH DISIPLIN KERJA, KOMPENSASI, MOTIVASI TERHADAP KINERJA KARYAWAN RSJD PROV. KEP BABEL - Lay, Avindo; Nurwanti, Nurwant (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The purpose of this study was to identify and analyze the influence of work discipline, compensation, motivation as independent variables on employee performance as the dependent variable at RSJD Provinsi Kepulauan Bangka Belitung.The form of research in this research is descriptive statistics and causality with multiple regression analysis method to test the hypothesis. The sampling technique used in this study was saturated sampling and used 55 non-health worker respondents with permanent civil servant status. The data for this study used primary data by distributing questionnaires to employees. The results of this study indicate that work discipline has no influence on the performance of the employees of RSJD Provinsi Kepulauan Bangka Belitung. While compensation and motivation have an influence on employee performance.